2022
DOI: 10.5116/ijme.62a5.96bf
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational instruction on medical student performance in simulation patient

Abstract: Objectives: This study aimed to evaluate the effects, and timing of, a video educational intervention on medical student performance in manikin-based simulation patient encounters. Methods: This prospective mixed-methods study was conducted as part of the University of Toledo College of Medicine and Life Sciences undergraduate medical curriculum. One hundred sixty-six students second-year students participated in two simulations on a single day in September 2021. A 7-minute video intervention outlining the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Examples of video-assisted learning in our settings are task trainers like venepuncture, electrocardiogram (ECG), injection pad, breast model, antenatal model and digital rectal examination (DRE) models combined with videos that show these procedures available for students to access in the self-directed learning area in the SC ( https://www.imu.edu.my/self-directed-learning-sdl/ ). Studies have previously reported that readily available educational video resources are an added instructional tool for students to practice skills and enable repetitive skills to reach clinical competency [ 23 , 24 ]. Our findings highlight the benefits of these resources for preclinical students through a self-directed learning approach.…”
Section: Preparation For Authentic Clinical Experiencementioning
confidence: 99%
“…Examples of video-assisted learning in our settings are task trainers like venepuncture, electrocardiogram (ECG), injection pad, breast model, antenatal model and digital rectal examination (DRE) models combined with videos that show these procedures available for students to access in the self-directed learning area in the SC ( https://www.imu.edu.my/self-directed-learning-sdl/ ). Studies have previously reported that readily available educational video resources are an added instructional tool for students to practice skills and enable repetitive skills to reach clinical competency [ 23 , 24 ]. Our findings highlight the benefits of these resources for preclinical students through a self-directed learning approach.…”
Section: Preparation For Authentic Clinical Experiencementioning
confidence: 99%
“…Three articles were on the e-learning platform and five were based on video-based elearning (Table 1). [26] in between simulation in two gropus standardized checklist clinical performance compared to relying solely on simulation-based learning.…”
Section: Figure 1: Prisma Flow Chart N -Number Of Studiesmentioning
confidence: 99%
“…In three studies [28,35,39], the evaluation was performed on the basis of MCQs and observed better performance and a better learning experience in the students. In another study [26], a standardized 44-point scale was used, which significantly improved student clinical performance. Two studies [27,37] used structured checklists and observed e-content as a preferred method.…”
Section: Table 1: Articles Included In the Studymentioning
confidence: 99%